Perovskite quantum dot glue as well as preparation method and application thereof

By adding fluorine-containing multifunctional ligands to perovskite quantum dispenser, the problem of insufficient water-oxygen resistance of perovskite quantum dispenser under high humidity and high temperature conditions is solved, and the superhydrophobic structure of the glue is realized, which significantly improves stability and water-resistant performance and reduces production costs.

CN119639413APending Publication Date: 2025-03-18WUXI UTMOST LIGHT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311202813.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing perovskite quantum dispenser has poor water-oxygen resistance under high humidity and high temperature conditions, and the use of high barrier water-oxygen diaphragms will increase costs, and the edges of the diaphragm are prone to failure.

Method used

By adding fluorine-containing multifunctional ligands to perovskite quantum dispenser, the coordination function interacts with the surface of perovskite quantum dots and combines with the glue components through hydrogen bonds to form a stable superhydrophobic structure.

Benefits of technology

The humidity and heat stability and water oxygen resistance of perovskite quantum dispenser are significantly improved, and the dependence on high-barrier water oxygen diaphragm is reduced, production costs are reduced, and the problem of diaphragm edge failure is alleviated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639413A_ABST
    Figure CN119639413A_ABST
Patent Text Reader

Abstract

The invention provides perovskite quantum dot glue as well as a preparation method and application thereof. The perovskite quantum dot glue comprises a glue body, perovskite quantum dots and a multifunctional ligand, wherein the glue body is filled with the perovskite quantum dots; the structure of the multifunctional ligand comprises a ligand functional group and a fluorine-containing group, and the ligand functional group is coordinated in uncoordinated lead ion vacancies in the perovskite quantum dots; the perovskite quantum dots are suspended in the glue through a multifunctional ligand forming coordination. According to the super-hydrophobic stable perovskite quantum dot glue provided by the invention, on the basis of ensuring excellent optical performance of perovskite quantum dots, the anti-aging stability, especially the damp-heat stability, of the perovskite quantum dot glue can be further improved, and a barrier film with a high water and oxygen barrier rate does not need to be used; and the condition of edge failure of the optical film can be effectively relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of display materials, and specifically relates to a perovskite quantum dot glue and a preparation method and application thereof. Background Art

[0002] As the requirements of optical devices for display technology continue to increase, perovskite quantum dots (molecular formula ABX3, where A is an organic cation, B is a metal ion, and X is a halogen group), as an advanced semiconductor optoelectronic material, have excellent optical properties such as high color purity, wide color gamut, high defect tolerance, ability to cover the entire spectrum, and high photoluminescence quantum yield. In recent years, a series of quantum dot display technologies and some related products have been incubated. Therefore, perovskite quantum dots have received widespread attention.

[0003] In the field of quantum dot display, compared with cadmium quantum dots, perovskite quantum dots have the following advantages: First, the preparation time of perovskite quantum dots is shorter. Compared with the traditional preparation method of cadmium quantum dots, perovskite quantum dots do not need to construct a core-shell structure during preparation, and the process is simpler and more suitable for industrial development; second, the emission peak half-width of perovskite quantum dots is narrower than that of cadmium quantum dots, and can cover a wider color gamut; finally, cadmium quantum dot series products are difficult to pass the mandatory ROHS certification standards formulated by the European Union, while perovskite quantum dots can easily pass the certification, and the latter has good application prospects.

[0004] At present, perovskite quantum dots can be combined with glue and water-oxygen barrier films to prepare perovskite quantum dot optical films, which are finally used in display modules or optical display devices. Display modules or optical display devices are usually used in harsh conditions such as strong light, high temperature and high humidity, especially humidity. The damage to perovskite quantum dots is particularly obvious. The water resistance of perovskite ionic crystals themselves is very poor. Although the water resistance can be maximized by using a water-oxygen barrier film with high barrier efficiency, on the one hand, the use of a high barrier water-oxygen barrier film will bring about the problem of high cost; on the other hand, even if the water-oxygen barrier efficiency of the membrane is improved, the problem of failure of the membrane edge still needs to be solved. Therefore, it is necessary to prepare a perovskite quantum dot glue with good water-oxygen resistance.

[0005] To this end, researchers have rationally optimized the glue components and tried to improve the stability of perovskite quantum dot glue in various aspects. For example, CN114311864A discloses a method for preparing a perovskite quantum dot polymer film. However, the resin prepared from the selected monomers can only simply encapsulate the perovskite quantum dots from a physical perspective, and cannot fundamentally reduce the surface defects of the perovskite quantum dots, and thus cannot improve its resistance to dry heat or blue light stability.

[0006] CN111410748A discloses a perovskite quantum dot composition. The different resins and monomers selected in the preparation of the perovskite quantum dot polymer film only play a simple physical packaging role for the quantum dots themselves during the curing process. The prepared optical film sample also has poor wet and heat stability, and water molecules can still easily enter and destroy the perovskite quantum dots.

[0007] It can be seen that the solutions disclosed in the prior art for improving the stability of perovskite quantum dot glue can only improve its resistance to blue light or high temperature. Generally speaking, the water resistance of the perovskite quantum dots themselves and the glue is not good; on the other hand, it is mainly prepared from the perspectives of surface coating and physical packaging, which causes high costs and is not conducive to industrial production. In addition, the structure of the encapsulated components is relatively complex, making it difficult to have more application scenarios.

[0008] Therefore, in this field, there is an urgent need to develop a perovskite quantum dot glue with good water and oxygen resistance and weather resistance to solve the above problems. Summary of the invention

[0009] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a perovskite quantum dot glue and a preparation method and application thereof. The present invention provides a super-hydrophobic stable perovskite quantum dot glue, which can further improve the aging stability, especially the wet heat stability, of the perovskite quantum dot glue on the basis of ensuring that the perovskite quantum dots have excellent optical properties, without the need to use a barrier film with a high water and oxygen barrier rate, and can effectively alleviate the failure of the edge of the optical film.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a perovskite quantum dot glue, the perovskite quantum dot glue comprising a glue body, perovskite quantum dots filled into the glue body, and a multifunctional ligand;

[0012] The structure of the multifunctional ligand comprises a ligand functional group and a fluorine-containing group, and the ligand functional group coordinates to the uncoordinated lead ion vacancy in the perovskite quantum dot;

[0013] The fluorine-containing group forms a hydrogen bond with the glue body, and the fluorine atoms in the fluorine-containing group repel the glue body or water molecules;

[0014] The perovskite quantum dots are suspended inside the glue by forming coordinated multifunctional ligands, and the main chains / side chains of several fluorine-containing groups are intertwined to form several repulsive pores, and the perovskite quantum dots in a suspended state or a free state are accommodated in the repulsive pores.

[0015] The present invention aims to solve the following technical problems existing in the prior art: (1) it is necessary to use a water-oxygen barrier film with high barrier efficiency to improve the water resistance of the membrane, resulting in high production costs; (2) the membrane prepared by using the water-oxygen barrier film with high barrier efficiency still has the problem of edge failure; (3) the water and oxygen resistance of the perovskite quantum dot glue itself is poor. The present invention obtains a stable super-hydrophobic perovskite quantum dot glue by adding a fluorine-containing multifunctional ligand, which has a synergistic effect with the perovskite quantum dots and the components in the glue.

[0016] Fluorinated multifunctional ligands play the following important roles in the preparation of glue: First, fluorinated multifunctional ligands containing specific types of functional groups can coordinate with uncoordinated lead ions in perovskite quantum dots, thereby effectively reducing the surface defects of perovskite quantum dots, thereby improving the stability of quantum dots themselves; second, the fluorinated groups in fluorinated multifunctional ligands easily form hydrogen bonds with N and O atoms in esters, urethanes, etc. in the glue, increasing the intermolecular forces and further improving the stability of the glue; finally, the dipoles of fluorinated groups cancel each other out, and they have lower polarity, which makes the surface energy of fluorinated compounds lower, so the fluorinated multifunctional ligands themselves have better hydrophobic properties. At the same time, when fluorine atoms are arranged, adjacent fluorine atoms repel each other, and the fluorine atoms are not in the same plane. The fluorine atoms in the main chain are distributed in a spiral along the carbon chain and tightly wrap the main chain, making it difficult for other atoms to embed. The above special spiral structure can fill the gaps between molecules in the glue and form a densely stacked hydrophobic structure. In addition, other functional groups in the fluorinated multifunctional ligand can also play a unique role in the perovskite quantum dot glue, such as passivating the quantum dot surface or cross-linking with the initiator in the glue component to improve the stability of the glue. Under the above multiple effects, the fluorinated multifunctional ligand can effectively resist water molecules, greatly improve the water resistance of the glue, and finally obtain stable super-hydrophobic perovskite quantum dots.

[0017] Preferably, the structural formula of the multifunctional ligand is CF p (CF2) n (CH2) m R, where CF3(CF2) n is a fluorine-containing group, R is a ligand functional group, R is selected from any one of a substituted or unsubstituted thiol group, a substituted or unsubstituted carboxyl group, a substituted or unsubstituted alkenyl group, a perfluoroalkyl group or a substituted or unsubstituted ester group, the value range of n is 2-17, and the value range of m is 2-8.

[0018] In the present invention, the value range of n is an integer of 2-17, for example, it can be 2, 4, 5, 7, 10, 13, 15, 17, etc.; the value range of m is an integer of 2-8, for example, it can be 2, 4, 5, 6, 7, 8.

[0019] In the present invention, by adjusting the value range of n and m, the stability of the perovskite quantum dot glue is significantly improved compared with the blank sample, especially the improvement of the hydrophobicity of the glue, which significantly improves its wet and hot stability and greatly reduces the degree of edge failure.

[0020] In the present invention, the structural formula of the multifunctional ligand is CF3(CF2) n (CH2) m R, wherein R can be selected from any one of a mercapto group, a carboxyl group, a perfluoroalkyl group or a carbon-carbon double bond functional group.

[0021] Preferably, the multifunctional ligand comprises at least one of the following characteristics:

[0022] (1) The multifunctional ligand is selected from any one of 1H, 1H, 2H, 2H-perfluoro-1-decyl mercaptan, perfluorohexadecanoic acid, nonafluoropentanoic acid, nonadecafluorodecanoic acid, 11H-perfluorodecanoic acid, 1H, 1H, 2H-perfluoro-1-dodecene, 2-(perfluorooctyl)ethyl methacrylate, 1H, 1H, 2H, 2H-heptadecafluorodecyl methacrylate, perfluorododecane or tridecafluorooctyl acrylate, or a combination of at least two thereof;

[0023] (2) The multifunctional ligand is selected from 1H, 1H, 2H, 2H-perfluoro-1-decanethiol.

[0024] Preferably, the structural formula of the perovskite quantum dots includes at least one of the following features:

[0025] (3) The structural formula of the perovskite quantum dot is ABCl x Br y I 3-x-y , wherein A is any one of Cs, FA or MA or a combination of at least two thereof, B is Pb or Sn, the value range of x is 0≤x≤3, for example, it can be 0, 1, 2, 3, etc.; the value range of y is 0≤y≤3, for example, it can be 0, 1, 2, 3, etc.;

[0026] (4) The structural formula of the perovskite quantum dots is FAPbBr3.

[0027] Preferably, the molar ratio of the multifunctional ligand to the perovskite quantum dots includes at least one of the following characteristics:

[0028] (5) The molar ratio of the multifunctional ligand to the perovskite quantum dots is 1:(0.1-10), wherein the specific value in (0.1-10) can be, for example, 0.1, 0.2, 0.3, 0.4, 0.6, 0.8, 1, 1.2, 1.6, 1.9, 2, 2.2, 2.5, 2.8, 3, 3.3, 3.5, 3.8, 4, 4.2, 4.3, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 5.9, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.4, 7.6, 7.8, 8, 8.1, 8.2, 8.5, 8.8, 9, 9.2, 9.4, 9.6, 9.8, 10, etc.;

[0029] (6) The molar ratio of the multifunctional ligand to the perovskite quantum dots is 1:1.

[0030] In the present invention, by regulating the molar ratio of the multifunctional ligand to the perovskite quantum dots, the multifunctional ligand can exert its optimal effect, thereby improving the stability of the perovskite quantum dot glue without affecting the optical properties of the quantum dots. If the molar ratio is too low, the effect of improving the stability of the glue will not be obvious, while if it is too high, the optical properties of the glue will be affected.

[0031] Preferably, the glue body comprises a polymer resin, and the polymer resin comprises at least one of the following characteristics:

[0032] (7) The polymer resin includes any one of modified or unmodified acrylic resin, modified or unmodified polyurethane resin, modified or unmodified epoxy resin or modified or unmodified silicone resin, or a combination of at least two thereof;

[0033] (8) The polymer resin is polyurethane acrylate resin.

[0034] Preferably, the molar ratio of the polymer resin to the perovskite quantum dots includes at least one of the following characteristics:

[0035] (9) The molar ratio of the polymer resin to the perovskite quantum dots is (100-400):1, for example, 100:1, 105:1, 110:1, 120:1, 150:1, 180:1, 200:1, 220:1, 250:1, 280:1, 300:1, 320:1, 350:1, 380:1, 400:1, etc.;

[0036] (10) The molar ratio of the polymer resin to the perovskite quantum dots is 100:1.

[0037] Preferably, the glue body further comprises diffusion particles, and the diffusion particles include organic silicon and / or inorganic oxides.

[0038] In the present invention, the inorganic oxide includes silicon dioxide and / or aluminum oxide.

[0039] Preferably, the molar ratio of the diffusion particles to the perovskite quantum dots includes at least one of the following characteristics:

[0041] (11) The molar ratio of the diffusion particles to the perovskite quantum dots is (10-40):1, for example, 10:1, 12:1, 15:1, 18:1, 20:1, 22:1, 25:1, 28:1, 30:1, 32:1, 35:1, 38:1, 40:1, etc.;

[0042] (12) The molar ratio of the diffused particles to the perovskite quantum dots is 10:1.

[0043] Preferably, the glue body further comprises monomers, which include acrylic monomers and / or olefin monomers. When the monomers are added to the glue, the monomers can polymerize to form a three-dimensional polymer network during the curing process of the glue, and the three-dimensional polymer network can further three-dimensionally wrap and physically encapsulate the suspended perovskite quantum dots or the free perovskite quantum dots, thereby further improving the waterproof performance of the perovskite quantum dots.

[0044] Preferably, the acrylic monomer comprises at least one of the following characteristics:

[0045] (13) The acrylic monomer includes any one of isobornyl acrylate, lauryl acrylate, n-butyl methacrylate, isooctyl methacrylate, isobornyl methacrylate, isodecyl methacrylate, lauryl methacrylate, hexanediol dimethacrylate, hexanediol diacrylate or trimethylolpropane triacrylate, or a combination of at least two thereof;

[0046] (14) The acrylic monomer is isobornyl acrylate.

[0047] Preferably, the olefin monomer includes styrene.

[0048] Preferably, the molar ratio of the monomer to the perovskite quantum dots includes at least one of the following characteristics:

[0049] (15) The molar ratio of the monomer to the perovskite quantum dots is (1-10):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.;

[0050] (16) The molar ratio of the monomer to the perovskite quantum dots is 1:1.

[0051] In the present invention, the glue further includes an initiator for being initiated to cure the glue, and the initiator includes a photoinitiator, such as 1173, TPO, and the like.

[0052] In a second aspect, the present invention provides a method for preparing the perovskite quantum dot glue according to the first aspect, the method comprising the following steps:

[0053] The glue body and the multifunctional ligand are mixed once to obtain a precursor material, and then the precursor material and the perovskite quantum dots are mixed for a second time to obtain the perovskite quantum dot glue.

[0054] The preparation process of the superhydrophobic perovskite quantum dot glue provided by the present invention is simple and easy to implement, with low cost, which is conducive to industrial-scale production. In addition, the selection range of glue components and multifunctional ligands is wide, and it can be applied to different types of quantum dots in different systems, and has a certain universality.

[0055] In the present invention, the molar ratio of the glue body, the multifunctional ligand and the perovskite quantum dots is (100-400):(0.1-10):1, preferably 100:1:1, for example, it can be 100:0.1:1, 105:0.5:1, 100:1:1, 110:2:1, 150:4:1, 200:6:1, 300:8:1, 400:10:1, etc.

[0056] Preferably, the precursor material further includes diffusion particles, monomers and initiators.

[0057] Preferably, the molar ratio of the glue body, the diffusion particles, the monomer, the multifunctional ligand, the initiator and the perovskite quantum dots includes at least one of the following characteristics:

[0058] (17) The molar ratio of the glue body, the diffusion particles, the monomer, the multifunctional ligand, the initiator and the perovskite quantum dots is (100-400):(10-40):(1-10):(0.1-10):(1-4):1, for example, it can be 100:10:1:0.1:1:1, 105:15:2:0.5:2:1, 110:20:3:3:3:1, 100:10:1:1:1:1, 200:30:8:8:4:1, 300:30:6:7:2:1, 400:40:10:10:4:1, etc.;

[0059] (18) The molar ratio of the glue body, the diffusion particles, the monomer, the multifunctional ligand, the initiator and the perovskite quantum dots is 100:10:1:1:1:1.

[0060] Preferably, the primary mixing is performed under stirring.

[0061] Preferably, the secondary mixing time is 10-60 min, preferably 30 min, for example, it can be 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.

[0062] In the present invention, by regulating the time of the secondary mixing, the multifunctional ligand is allowed to fully interact with the surface of the perovskite quantum dots and the glue component, thereby achieving the maximum effect.

[0063] Preferably, the secondary mixing further includes a degassing treatment.

[0064] In a third aspect, the present invention provides a perovskite quantum dot optical film, comprising a perovskite quantum dot glue layer and an optical film layer arranged on at least one side of the perovskite quantum dot glue layer, wherein the perovskite quantum dot glue layer is obtained by curing the perovskite quantum dot glue according to the first aspect.

[0065] In a fourth aspect, the present invention provides an optical display device, comprising the perovskite quantum dot optical film according to the third aspect.

[0066] The optical display device provided by the present invention can effectively improve the water resistance of the perovskite quantum dot glue without using a barrier film with a high water and oxygen barrier rate, greatly saving costs, and does not require bulky physical packaging, saving space for the preparation of display modules and devices, and has greater application potential.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] The invention provides a perovskite quantum dot glue, which is prepared by adding a fluorine-containing multifunctional ligand and having a synergistic effect with the perovskite quantum dots and other components in the glue to obtain a stable super-hydrophobic perovskite quantum dot glue.

[0069] Fluorinated multifunctional ligands play the following important roles in the preparation of glue: First, fluorinated multifunctional ligands containing specific types of functional groups can coordinate with uncoordinated lead ions in perovskite quantum dots, thereby effectively reducing the surface defects of perovskite quantum dots, thereby improving the stability of quantum dots themselves; second, the fluorinated groups in fluorinated multifunctional ligands easily form hydrogen bonds with N and O atomic components in esters, urethanes, etc. in the glue, increasing the intermolecular forces and further improving the stability of the glue; finally, the fluorinated groups have their dipoles offset each other and have lower polarity, making the surface energy of fluorinated compounds lower, so the fluorinated multifunctional ligands themselves have better hydrophobic properties. At the same time, when fluorine atoms are arranged, adjacent fluorine atoms repel each other, and the fluorine atoms are not in the same plane. The fluorine atoms in the main chain are distributed in a spiral along the carbon chain and tightly wrap the main chain, making it difficult for other atoms to embed. The above special spiral structure can fill the gaps between molecules in the glue and form a densely stacked hydrophobic structure. In addition, other functional groups in the fluorinated multifunctional ligand can also play a unique role in the perovskite quantum dot glue, such as passivating the quantum dot surface or cross-linking with the initiator in the glue component to improve the stability of the glue. Under the above multiple effects, the fluorinated multifunctional ligand can effectively resist water molecules, greatly improve the water resistance of the glue, and finally obtain stable super-hydrophobic perovskite quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 Schematic diagram of the preparation of the perovskite quantum dot glue provided in Example 1;

[0071] Figure 2 Schematic diagram of the formation process of the perovskite quantum dot glue provided in Example 1. DETAILED DESCRIPTION

[0072] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0073] Example 1

[0074] This embodiment provides a perovskite quantum dot glue, which includes FAPbBr3 perovskite quantum dots, polyurethane acrylate, aluminum oxide diffusion particles, 1H,1H,2H,2H-perfluorododecanethiol and photoinitiator 1173 in a molar ratio of 1:100:10:1:1.

[0075] This embodiment also provides a method for preparing the above-mentioned perovskite quantum dot glue, such as Figure 1-2 As shown, it includes the following steps:

[0076] (1) FAPbBr3 quantum dots were prepared by using oleic acid ligands combined with a traditional hot injection method. Specifically, 0.416 g of formamidine acetate, 0.75 g of lead acetate, 5 mL of oleic acid and 50 mL of octadecene were weighed, nitrogen was introduced after degassing and the temperature was raised to 120°C, 1.74 g of oleylamine bromide dissolved in toluene in advance was injected, and after reacting for 5 seconds, an ice-water bath was used to obtain a crude perovskite quantum dot solution, which was then centrifuged with ethyl acetate and toluene to obtain a quantum dot purified solution. 10 mL of the purified liquid was centrifuged with ethyl acetate and the remaining solvent was removed to obtain a perovskite quantum dot precipitate;

[0077] (2) Weighing 20 g of polyurethane acrylate, 2 g of aluminum oxide diffusion particles and 200 mg of photoinitiator 1173, and then mixing them with 200 mg of 1H,1H,2H,2H-perfluorododecanethiol to obtain a precursor material;

[0078] (3) 200 mg of the perovskite quantum dot precipitate in step (1) and the precursor material in step (2) were stirred for 30 min, placed in a degassing machine and vacuum centrifuged for 5 min to obtain perovskite quantum dot glue.

[0079] Example 2

[0080] The difference between this embodiment and embodiment 1 is that the polyurethane acrylate in step (2) is replaced by fluorosilicone-modified polyurethane acrylate, and the rest is the same as embodiment 1.

[0081] Example 3

[0082] The difference between this embodiment and embodiment 1 is that in step (2), 1H,1H,2H,2H-perfluorododecanethiol is replaced by perfluorohexadecanoic acid, and the rest is the same as embodiment 1.

[0083] Example 4

[0084] The difference between this embodiment and embodiment 1 is that in step (2), 1H,1H,2H,2H-perfluorododecanethiol is replaced by perfluorododecane, and the rest is the same as embodiment 1.

[0085] Example 5

[0086] The difference between this embodiment and embodiment 1 is that in step (1), 0.416 g of formamidine acetate is replaced by 0.215 g of cesium carbonate, and the rest is the same as embodiment 1.

[0087] Example 6

[0088] The difference between this embodiment and embodiment 1 is that the stirring for 30 min in step (3) is replaced by stirring for 60 min, and the rest is the same as embodiment 1.

[0089] Example 7

[0090] The difference between this embodiment and embodiment 1 is that the amount of 1H,1H,2H,2H-perfluorododecanethiol in step (1) is replaced by 10 mg, and the rest is the same as embodiment 1.

[0091] Example 8

[0092] The difference between this embodiment and embodiment 1 is that the amount of 1H,1H,2H,2H-perfluorododecanethiol in step (1) is replaced with 2200 mg, and the rest is the same as embodiment 1.

[0093] Example 9

[0094] The difference between this embodiment and embodiment 1 is that 200 mg of isobornyl acrylate is added, and the rest is the same as embodiment 1.

[0095] Comparative Example 1

[0096] The difference between this comparative example and Example 1 is that 1H,1H,2H,2H-perfluorododecanethiol is not added in step (1), and the rest is the same as Example 1.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is that 1H,1H,2H,2H-perfluorododecanethiol in step (1) is replaced by 2,2,2-trifluoroethanethiol, and the rest is the same as Example 1.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 1 is that in step (2), 1H,1H,2H,2H-perfluorododecanethiol is replaced by n-dodecyl mercaptan, and the rest is the same as Example 1.

[0101] Application Examples 1 to 9 and Comparative Application Examples 1 to 3

[0102] A perovskite quantum dot optical film comprises a first water-oxygen barrier film (thickness 130 μm), a perovskite quantum dot glue layer (thickness 40 μm) and a second water-oxygen barrier film (thickness 130 μm) stacked in sequence; the material of the perovskite quantum dot glue layer comprises the perovskite quantum dot glue provided in Examples 1-9 and Comparative Examples 1-3; the preparation method of the perovskite quantum dot optical film comprises:

[0103] Perovskite quantum dot glue is coated on the surface of the first water and oxygen barrier film, and the second water and oxygen barrier film is compounded, and the film is irradiated under 365nm, 2000W ultraviolet light for 1 minute for curing to obtain the perovskite quantum dot optical film.

[0104] Test conditions

[0105] The perovskite quantum dot optical films provided in Application Examples 1 to 9 and Comparative Application Examples 1 to 3 were tested, and the testing method was as follows:

[0106] (1) Photoluminescence quantum yield: The fluorescence spectrometer was used for testing and data analysis. The test and analysis instrument model is FLS1000.

[0107] (2) Blue light aging resistance: A blue light LED panel with a wavelength of 450-455nm was used to irradiate the perovskite quantum dot optical film, and the time taken for the brightness to drop by 10% (T90) was recorded;

[0108] (3) Dry heat aging resistance: The perovskite quantum dot optical film was placed in a constant temperature box set at 85°C, and the time taken for the brightness to drop by 10% (T90) was recorded;

[0109] (4) Resistance to moisture and heat aging: The perovskite quantum dot optical film was placed in a constant humidity and thermostatic box with a temperature set at 85°C and a humidity set at 85%. The temperature was set at 85°C, and the time taken for the brightness to drop by 10% (T90) was recorded.

[0110] (5) Edge failure test: Use a vernier caliper to test the edge failure width.

[0111] The test results are shown in Table 1:

[0112] Table 1

[0113]

[0114] As can be seen from Table 1, the perovskite quantum dot glue provided by the present invention greatly improves the stability of the perovskite quantum dot glue and its membrane, especially the water and oxygen resistance, through the action of the multifunctional ligand such as perfluoro compound on the glue component and the surface of the perovskite quantum dot, and the degree of edge failure is also effectively alleviated.

[0115] From Application Example 1 and Application Example 2 combined with the comparison of Application Example 1, it can be seen that this system has an optimization effect on different types of resins;

[0116] From Application Example 1, Application Example 3, Application Example 4 and Comparative Application Example 3 combined with Comparative Application Example 1, it can be seen that the perfluorinated group significantly improves the wet heat aging stability of the glue, and the perfluorinated groups with different functional groups also have different effects, among which the mercapto group has the greatest improvement on the stability of the glue;

[0117] It can be seen from Application Examples 1 and 5 that this system is also effective for CsPbBr3 perovskite quantum dot glue;

[0118] From Application Examples 1 and 6, it can be seen that extending the stirring time also has a small impact on the optical performance and stability of the film, but as long as it is within a suitable range, relatively good results can be achieved;

[0119] It can be seen from Application Examples 1 and 9 that adding monomers can further improve the aging resistance of the glue, but not too much monomers can be added, otherwise the fluorescence effect will be affected.

[0120] It can be seen from Application Examples 1, 7 and 8 that the mass ratio of the amount of perovskite quantum dots to the multifunctional ligand is not within the preferred range of the present invention. The amount of multifunctional ligand added is too small. Although it has no obvious effect on the quantum yield, the blue light resistance and dry heat aging resistance are worse. If the amount of multifunctional ligand added is too much, the quantum yield of the membrane will be seriously affected, and the aging stability will be poor.

[0121] It can be seen from Application Example 1 and Comparative Application Example 2 that the perfluoro group plays a vital role in improving the water and oxygen resistance of the glue, and when the length of the fluorocarbon chain is not within the preferred range of the present invention, it is difficult to achieve the effect of improving the stability and optical properties of the glue;

[0122] In summary, the perovskite quantum dot glue provided by the present invention avoids the problem of many surface defects of conventional perovskite quantum dots. At the same time, the perfluorinated compound is compounded with the components in the resin to improve the stability of the glue, especially the water and oxygen resistance. In addition, the multifunctional ligand has strong applicability, simple preparation process, low cost, and can realize industrial production.

[0123] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A perovskite quantum dot glue, characterized in that: The perovskite quantum dot glue comprises a glue body, perovskite quantum dots filled into the glue body, and a multifunctional ligand; The structure of the multifunctional ligand comprises a ligand functional group and a fluorine-containing group, and the ligand functional group is coordinated to the uncoordinated lead ion vacancy in the perovskite quantum dot; The fluorine-containing group forms a hydrogen bond with the glue body, and the fluorine atoms in the fluorine-containing group repel the glue body or water molecules; The perovskite quantum dots are suspended inside the glue by forming coordinated multifunctional ligands, and the main chains / side chains of several fluorine-containing groups are intertwined to form several repulsive pores, and the perovskite quantum dots in a suspended state or a free state are accommodated in the repulsive pores.

2. The perovskite quantum dot glue according to claim 1, characterized in that The structural formula of the multifunctional ligand is CF3(CF2) n (CH2) m R, where CF3(CF2) n is a fluorine-containing group, R is a ligand functional group, R is selected from any one of a substituted or unsubstituted thiol group, a substituted or unsubstituted carboxyl group, a substituted or unsubstituted alkenyl group, a perfluoroalkyl group or a substituted or unsubstituted ester group, the value range of n is 2-17, and the value range of m is 2-8.

3. The perovskite quantum dot glue according to claim 1 or 2, characterized in that: The multifunctional ligand comprises at least one of the following characteristics: (1) The multifunctional ligand is selected from any one of 1H, 1H, 2H, 2H-perfluoro-1-decyl mercaptan, perfluorohexadecanoic acid, nonafluoropentanoic acid, nonadecafluorodecanoic acid, 11H-perfluorodecanoic acid, 1H, 1H, 2H-perfluoro-1-dodecene, 2-(perfluorooctyl)ethyl methacrylate, 1H, 1H, 2H, 2H-heptadecafluorodecyl methacrylate, perfluorododecane or tridecafluorooctyl acrylate, or a combination of at least two thereof; (2) The multifunctional ligand is selected from 1H, 1H, 2H, 2H-perfluoro-1-decanethiol.

4. The perovskite quantum dot glue according to any one of claims 1 to 3, characterized in that: The structural formula of the perovskite quantum dot includes at least one of the following characteristics: (3) The structural formula of the perovskite quantum dot is ABCl x Br y I 3-x-y , where A is any one of Cs, FA or MA or a combination of at least two of them, B is Pb or Sn, the value range of x is 0≤x≤3, and the value range of y is 0≤y≤3; (4) The structural formula of the perovskite quantum dots is FAPbBr3; The molar ratio of the multifunctional ligand to the perovskite quantum dots includes at least one of the following characteristics: (5) The molar ratio of the multifunctional ligand to the perovskite quantum dots is (0.1-10):1; (6) The molar ratio of the multifunctional ligand to the perovskite quantum dots is 1:

1.

5. The perovskite quantum dot glue according to any one of claims 1 to 4, characterized in that: The glue body comprises a polymer resin, and the polymer resin comprises at least one of the following characteristics: (7) The polymer resin includes any one of modified or unmodified acrylic resin, modified or unmodified polyurethane resin, modified or unmodified epoxy resin or modified or unmodified silicone resin, or a combination of at least two thereof; (8) The polymer resin is polyurethane acrylate resin; The molar ratio of the polymer resin to the perovskite quantum dots includes at least one of the following characteristics: (9) The molar ratio of the polymer resin to the perovskite quantum dots is (100-400):1; (10) The molar ratio of the polymer resin to the perovskite quantum dots is 100:1; The glue body further comprises diffusion particles, wherein the diffusion particles include organic silicon and / or inorganic oxides; The molar ratio of the diffusion particles to the perovskite quantum dots includes at least one of the following characteristics: (11) The molar ratio of the diffusion particles to the perovskite quantum dots is (10-40):1; (12) The molar ratio of the diffused particles to the perovskite quantum dots is 10:

1.

6. The perovskite quantum dot glue according to any one of claims 1-5, characterized in that: The glue body also contains monomers, which include acrylic monomers and / or olefin monomers; The acrylic monomer comprises at least one of the following characteristics: (13) The acrylic monomer includes any one of isobornyl acrylate, lauryl acrylate, n-butyl methacrylate, isooctyl methacrylate, isobornyl methacrylate, isodecyl methacrylate, lauryl methacrylate, hexanediol dimethacrylate, hexanediol diacrylate or trimethylolpropane triacrylate, or a combination of at least two thereof; (14) The acrylic monomer is isobornyl acrylate; The olefin monomer includes styrene; The molar ratio of the monomer to the perovskite quantum dots includes at least one of the following characteristics: (15) The molar ratio of the monomer to the perovskite quantum dots is (1-10):1; (16) The molar ratio of the monomer to the perovskite quantum dots is 1:

1.

7. A method for preparing the perovskite quantum dot glue according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: The glue body and the multifunctional ligand are mixed once to obtain a precursor material, and then the precursor material and the perovskite quantum dots are mixed for a second time to obtain the perovskite quantum dot glue.

8. The method according to claim 7, characterized in that The precursor material also includes diffusion particles, monomers and initiators; The molar ratio of the glue body, the diffusion particles, the monomer, the multifunctional ligand, the initiator and the perovskite quantum dots includes at least one of the following characteristics: (17) The molar ratio of the glue body, the diffusion particles, the monomer, the multifunctional ligand, the initiator and the perovskite quantum dots is (100-400):(10-40):(1-10):(0.1-10):(1-4):1; (18) The molar ratio of the glue body, the diffusion particles, the monomer, the multifunctional ligand, the initiator and the perovskite quantum dots is 100:10:1:1:1:1; The primary mixing is carried out under stirring; The secondary mixing time is 10-60min; The secondary mixing also includes a degassing process.

9. A perovskite quantum dot optical film, characterized in that: The perovskite quantum dot optical film includes a perovskite quantum dot glue layer and an optical film layer arranged on at least one side of the perovskite quantum dot glue layer, and the perovskite quantum dot glue layer is obtained by curing the perovskite quantum dot glue according to any one of claims 1-6.

10. An optical display device, characterized in that: The optical display device comprises the perovskite quantum dot optical film according to claim 9.

Citation Information

Patent Citations

  • Perovskite quantum dot composition, preparation method of perovskite quantum dot composition, perovskite quantum dot film and preparation method of perovskite quantum dot film

    CN111410748A

  • Preparation method of perovskite quantum dot polymer film

    CN114311864A